Answer:
f average = 1
smaller value c = 3
larger value c = 5
Step-by-step explanation:
Answer:
C) a sample distribution of a sample mean with n = 10

and 
Step-by-step explanation:
Here, the random experiment is rolling 10, 6 faced (with faces numbered from 1 to 6) fair dice and recording the average of the numbers which comes up and the experiment is repeated 20 times.So, here sample size, n = 20 .
Let,
= The number which comes up on the ith die on the jth trial.
∀ i = 1(1)10 and j = 1(1)20
Then,
= 
= 3.5 ∀ i = 1(1)10 and j = 1(1)20
and,
= 
= 
= 
15.166667
so,
= 

= 2.91667
and
= ![\sqrt {2.91667}[/tex [tex]\simeq 1.7078261036](https://tex.z-dn.net/?f=%5Csqrt%20%7B2.91667%7D%5B%2Ftex%3C%2Fp%3E%3Cp%3E%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%5Btex%5D%5Csimeq%201.7078261036)
Now we get that,

We get that
are iid RV's ∀ j = 1(1)20
Let, 
So, we get that 
=
for any i = 1(1)10
= 3.5
and,
![\sigma_{({\overline}{Y})} = \frac {\sigma_{Y_{j}}}{\sqrt {20}} = \frac {\sigma_{X_{ij}}}{\sqrt {20}} = \frac {1.7078261036}{\sqrt {20}} [tex]\simeq 0.38](https://tex.z-dn.net/?f=%5Csigma_%7B%28%7B%5Coverline%7D%7BY%7D%29%7D%20%3D%20%5Cfrac%20%7B%5Csigma_%7BY_%7Bj%7D%7D%7D%7B%5Csqrt%20%7B20%7D%7D%3C%2Fp%3E%3Cp%3E%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%3D%20%5Cfrac%20%7B%5Csigma_%7BX_%7Bij%7D%7D%7D%7B%5Csqrt%20%7B20%7D%7D%3C%2Fp%3E%3Cp%3E%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%3D%20%5Cfrac%20%7B1.7078261036%7D%7B%5Csqrt%20%7B20%7D%7D%3C%2Fp%3E%3Cp%3E%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%20%5Btex%5D%5Csimeq%200.38)
Hence, the option which best describes the distribution being simulated is given by,
C) a sample distribution of a sample mean with n = 10

and 
Answer:
the ansmwer is * grabs a notebook and doodle the equation* hmm.. it is 7m
happy to help!!!
A^2+b^2=c^2 so 4(4) +3(3) is 16+9= 25 and the square root of that is 5.
F(x)=(-2/((x+y-2)^(1/2))-(x+y+2)^(1/2)
the only irrational part of this expression is the (x+y-2)^(1/2) in the denominator, so, to rationalize this, you multiply the numerator and denominator by the denominator, as well as the other parts of the expression
also, you must multiply the -sqrt(x+y+2) by sqrt(x+y-2)/sqrt(x+y-2) to form a common denominator
(-2)/(x+y-2)^(1/2)-(x+y+2)^(1/2)(x+y-2)^(1/2)/(x+y-2)^(1/2)
(common denominator)
(-2-(x^2+xy+2x+xy+y^2+2y-2x-2y-4))/(x+y-2)^(1/2)
(FOIL)
(-2-x^2-y^2-2xy+4)/(x+y-2)^(1/2)
(Distribute negative)
(-x^2-y^2-2xy+2)/(x+y-2)^(1/2)
(Simplify numerator)
(-x^2-y^2-2xy+2)(x+y-2)^(1/2)/(x+y-2)^(1/2)(x+y-2)^(1/2)
(Rationalize denominator by multiplying both top and bottom by sqrt)
(-x^2-y^2-2xy+2)((x+y-2)^(1/2))/(x+y-2)
(The function is now rational)
=(-x^2-y^2-2xy+2)(sqrt(x+y-2))/(x+y-2)